2006
DOI: 10.1111/j.1468-2389.2006.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Faking Likelihood in the Employment Interview

Abstract: There has been surprisingly little research on faking in the employment interview, despite the fact that professional judgment would suggest that faking might occur in the interview. Based on a review of the literature on faking in personality tests and the literature on deception, we propose a model of faking during an employment interview and develop 19 testable propositions to guide future research. We argue that faking is a function of capacity, willingness, and opportunity to fake. Structured interviews p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
345
7
7

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(383 citation statements)
references
References 144 publications
(205 reference statements)
24
345
7
7
Order By: Relevance
“…The higher the extraversion score, the higher the motivation to fake. These findings are consistent with Levashina and Campion (2006) that extraversion can lead to faking action.…”
Section: Hypotheses Testingsupporting
confidence: 91%
See 2 more Smart Citations
“…The higher the extraversion score, the higher the motivation to fake. These findings are consistent with Levashina and Campion (2006) that extraversion can lead to faking action.…”
Section: Hypotheses Testingsupporting
confidence: 91%
“…A previous research by Levashina & Campion (2006) showed that faking is a function of capacity, willingness, and opportunity to fake. Levashina and Campion (2006) also mentioned that some other structures or components may increase the faking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…D. Maurer et al, 1999) or choices (e.g., Janz, 1989). Making interviewees explicitly aware of an interview's requirements, however, might tempt them to say whatever they were made to believe the interviewers wanted to hear-even though these answers might bear no relation to the behavior exhibited once interviewees actually face the situations described (Levashina & Campion, 2006).…”
Section: Consequences Of Interview Transparency On Criterion-related mentioning
confidence: 99%
“…Qualitative Studien zu Faking belegen, dass Personen in denselben Situationen unterschiedlich faken (Hell & Schuler, 2005) und aussagekräftig sind -sind für Faking anfällig (Levashina & Campion, 2006;Levashina & Campion, 2007). Sogar bei Integritätstests und Tests mit biographischen Inhalten konnte Faking nachgewiesen werden .…”
Section: Theoretischer Hintergrundunclassified